Answer:
-13
Step-by-step explanation:
We remove the -4 by adding 4 to each side:
3y = -43 + 4
Now we simplify to give:
3y = -39
So now we divide both sides by 3 to give our answer of:
y = -39/3
y = -13
We can substitute this into the original equation to check our answer:
-4 + 3(-13) = -43
-4 + -39 = -43
✅
Answer:
BBBBB
Step-by-step explanation:
Answer:
w = 12
Step-by-step explanation:
W=48/4
W=12 ANS. FOR THE WIDTH.
L=12+8=20 ANS. FOR THE LENGTH.
PROOF:
2*20+2*12=64
40+24=64
64=64
Answer:
n = 23
Step-by-step explanation:
-8 + n = 15
-8 + n + 8 = 15 + 8
n = 23
Answer: n = 23